The Effect of Wheatley’s Model on Learning Some Mixed Skills in Soccer for Preparatory School Students - Mohammed, Yousif; Salahaldeen , Mostafa (Journal of Physical Education, 2023)
The research aimed at designing teaching units according to wheatley’s model for learning some mixed soccer skills as well as identifying the effect of this model on learning these skills. The researchers used the experimental method on (99) fourth grade Al Kuld preparatory school students for boys. Three mixed skills were selected; trapping – passing, dribbling – passing, and trapping – dribbling – scoring. A pilot study was applied on (10) students followed by the pretests then the application of the teaching program for 8 weeks with 16 teaching sessions for each group. The data was collected and treated using proper statistical operations to conclude that wheatley’s model have a positive effect in learning mixed skills in soccer. In addition to that, they concluded that the experimental group surpassed the controlling group in posttests.